Gemeinwohlorientiert und innovativ? : Die Förderung politischer Jugendbildung durch unternehmensnahe Stiftungen - Hirsch, Anja (2019)
Business-related foundations are increasingly appearing to serve the common good as financiers of political education and are also promoting innovative formats aimed at "disadvantaged young people". So far, little is known about how these foundations are intertwined with corporate interests and what understanding of maturity is the basis of their educational work. Based on critical emancipatory theories of society and education, Anja Hirsch shows how the connection with companies can affect programs of company-related foundations and how innovative formats of political youth education reproduce inequality relationships.